2022
DOI: 10.3389/fbioe.2022.1087656
|View full text |Cite
|
Sign up to set email alerts
|

Generation of multicellular tumor spheroids with micro-well array for anticancer drug combination screening based on a valuable biomarker of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a highly malignant tumor with a poor prognosis. More than 30% of patients with diagnosed HCC have abnormally high expression of fibroblast growth factor receptor 4 (FGFR4). Currently, clinical trials for a variety of FGFR4-specific inhibitors have started. However, the effect of these inhibitors is not ideal, and it is necessary to find a drug combination to synergistically exert anti-tumor effects. We found strong correlations between FGFR4 and HCC clinicopathological charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Risk stratification of hepatocellular carcinoma, including risk stratification algorithms and biomarkers, could help improve the effectiveness of HCC treatment by better identifying at-risk individuals [ 49 ]. In addition, the combination of valuable hepatocellular carcinoma biomarkers after screening into an array has positive significance in clinical application [ 50 ]. Due to the heterogeneity of tumors and individuals, a large enough biomarker pool is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Risk stratification of hepatocellular carcinoma, including risk stratification algorithms and biomarkers, could help improve the effectiveness of HCC treatment by better identifying at-risk individuals [ 49 ]. In addition, the combination of valuable hepatocellular carcinoma biomarkers after screening into an array has positive significance in clinical application [ 50 ]. Due to the heterogeneity of tumors and individuals, a large enough biomarker pool is needed.…”
Section: Discussionmentioning
confidence: 99%
“…For cancer research, MCTS models serve as a transition between in vivo tumor models and in vitro cultured cancer cells (33,34).…”
Section: Challenges In Using Model Systems To Recapitulate Liver Diseasementioning
confidence: 99%
“…In addition, Wang Q. et al produced MCTSs of uniform size using agarose hydrogel microwells. They demonstrated that this platform is accurate, efficient, and reproducible for determining the efficacy of candidate drugs to treat cancer, and they used the platform to show that parthenolide may increase the efficacy of inhibitors that act on the FGFR4 receptor (34).…”
Section: Anti-cancermentioning
confidence: 99%